Qaraqalpaq Baqsíshílíq Óneri Arqalí Oqíwshí Jaslardíń Estetikalíq Tárbiyasín Rawajlandíríw - Gulasen, Najimatdinova; Lola, Maxamatdinova (Miasto Przyszłości, 2023)
In the cast of the Karakalpak epic includes a number of fats, melons and kischinev. Each of them appeared in specific socio-political conditions, as well as the content of the epic in the repertoire of each other.